Enhancing reflection and empathy skills via using a virtual reality based learning framework - Stavroulia, Kalliopi Evangelia; Lanitis, Andreas (My University, 2019)
The last few years Virtual Reality (VR) based approaches have emerged as a new education paradigm. This paper addresses the possibility to cultivate reflection and empathy skills using a VR based framework targeting to maximize the professional development of teachers. Reflection and empathy are skills of paramount importance for teachers and an integral part of their professional development. The current research aims to investigate possible differences in cultivating reflection and empathy skills between participants who used a VR system and the control group who were trained in a real classroom environment. Experimental results indicate that the participants using the virtual classroom environment were able to better reflect and empathize with the students whereas participants from the control group tended to be more undecided. Moreover, the VR system gave the participants the opportunity to enter the students' virtual body and understand the different perspectives affecting at a higher level the reflection process than the control group.
Keywords: Teachers; Reflection; Empathy; Virtual reality